The Study Of The Application Of Noise Mapping Using Golden Surfer Software To Control Noise - Mas'idah, Eli; Marlyana, Novi (Universitas Islam Sultan Agung, 2022)
Machines and equipment or work processes that make noise. Evaluation of noise intensity is carried out by making a noise map that describes the noise distribution pattern from 278 measurement points and then processed with surfer software, which then becomes basic information to protect workers from the risk of hearing loss. After measuring and analyzing the data, the noise level ranged from the lowest of 41.0 dBA, to the highest of 101.9 dBA. From the noise map, it can be seen that the main sources of noise are in the workshop area, corn intake & dryer area, generator area & bagging off area. Noise control efforts have been carried out by engineering controls, administrative controls in the form of work rotation, Standard Operating Procedures, training, safety signs and the use of ear protective equipment for workers in the form of earplugs and earmuffs.